Propagation Characteristics and Magnetic Field Distribution of Rotating Magnet-Based Mechanical Antenna in the Air-Seawater-Seabed Three-Layer Medium - S. P. Chen; Q. Zhou; J. Y. Zhang; S. Y. Wang (International Journal of Antennas and Propagation)
Aiming at the application requirements of underwater cross-domain communication, based on the equivalent relationship between the rotating permanent magnet and the orthogonal time-varying current loop, this paper establishes an air-seawater-seabed three-layer medium model and analyzes the magnetic field distribution and propagation characteristics of the rotating permanent magnet-based mechanical antenna (RMBMA). Based on the electromagnetic field simulation software FEKO, the influence of vertical rotation and horizontal rotation of RMBMA on the radiation magnetic field is analyzed. The magnetic field distribution and magnetic field attenuation characteristics of RMBMA at different depths are obtained by simulation. The influence of RMBMA operating frequency and magnetic moment on the propagation characteristics is studied. The research shows that the horizontal rotation of the magnetic source is better than the vertical rotation in the long-distance underwater communication. When the magnetic source and the receiving point are close to the interface of the medium, the magnetic field strength and the propagation distance can be relatively increased. With appropriate frequency and magnetic moment, the magnetic field strength and communication distance can be further increased.